2021
DOI: 10.3390/jcm10245762
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Chronic Wounds with Platelet-Derived Growth Factors from Single Donor Platelet-Rich Plasma following One Freeze-Thaw Cycle. A Cross-Sectional Study

Abstract: Chronic non-healing wounds (CNHWs) may be associated with trauma or idiopathic in nature and are difficult to treat. Our objective was to assess the use of platelet-derived growth factor (PDGF) from single-donor platelets (al-PRP), using one freeze-thaw cycle, for treating CNHWs. We conducted a cross-sectional study. A total of 23 CNHWs being treated with al-PRP. The al-PRP treatment can be considered successful in well over half (n = 13, 56.5%) of the wounds. We found that all the wounds treated for up to 7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Studies have reported positive results of wound healing upon treatment with autologous platelets. The majority of patients whose platelet treatment continued for more than three months showed complete healing and reported fewer adverse events [35,36]. The major disadvantage of using autologous platelets therapeutically centers around the large-volume blood withdrawals required to isolate the platelets which may give rise to severe adverse effects, such as hemodynamic instability in patients with chronic wounds, bleeding disorders, or anemic conditions [37].…”
Section: Plateletsmentioning
confidence: 99%
“…Studies have reported positive results of wound healing upon treatment with autologous platelets. The majority of patients whose platelet treatment continued for more than three months showed complete healing and reported fewer adverse events [35,36]. The major disadvantage of using autologous platelets therapeutically centers around the large-volume blood withdrawals required to isolate the platelets which may give rise to severe adverse effects, such as hemodynamic instability in patients with chronic wounds, bleeding disorders, or anemic conditions [37].…”
Section: Plateletsmentioning
confidence: 99%